The effects of exposure to pyriproxyfen and predation on Zika virus infection and transmission in Aedes aegypti. - Abdullah A Alomar; Bradley H Eastmond; Barry W Alto (Public Library of Science (PLoS), 2020)
Zika virus (ZIKV) is an emerging mosquito-borne pathogen that can cause global public health threats. In the absence of effective antiviral medications, prevention measures rely largely on reducing the number of adult mosquito vectors by targeting juvenile stages. Despite the importance of juvenile mosquito control measures in reducing adult population size, a full understanding of the effects of these measures in determining mosquito phenotypic traits and in mosquito-arbovirus interactions is poorly understood. Pyriproxyfen is a juvenile hormone analog that primarily blocks adult emergence, but does not cause mortality in larvae. This mechanism has the potential to work in combination with other juvenile sources of mortality in nature such as predation to affect mosquito populations. Here, we experimentally evaluated the effects of juvenile exposure to pyriproxyfen and predatory mosquito Toxorhynchites rutilus on Aedes aegypti phenotypes including susceptibility to ZIKV infection and transmission. We discovered that combined effects of pyriproxyfen and Tx. rutilus led to higher inhibition of adult emergence in Ae. aegypti than observed in pyriproxyfen or Tx. rutilus treatments alone. Adult body size was larger in treatments containing Tx. rutilus and in treatments mimicking the daily mortality of predation compared to control or pyriproxyfen treatments. Susceptibility to infection with ZIKV in Ae. aegypti was reduced in predator treatment relative to those exposed to pyriproxyfen. Disseminated infection, transmission, and titers of ZIKV in Ae. aegypti were similar in all treatments relative to controls. Our data suggest that the combination of pyriproxyfen and Tx. rutilus can inhibit adult Ae. aegypti emergence but may confer a fitness advantage in survivors and does not inhibit their vector competence for ZIKV relative to controls. Understanding the ultimate consequences of juvenile mosquito control measures on subsequent adults' ability to transmit pathogens is critical to fully understand their overall impacts.